Morphometric study of the isthmus of the thyroid gland in Bangladeshi cadaver - Nurunnabi, Abu Sadat Mohammad; Mahbub, S; Perven, HA; Ara, S (Nepal Journal of Medical Sciences, 2013)
Background: The position and size of isthmus of thyroid vary greatly in humans, and sometimes it is absent. The present study was designed to find out the difference in isthmus of the thyroid gland of Bangladeshi people in relation to age and sex. Methods: The cross-sectional, descriptive study was performed in the Department of Anatomy, Dhaka Medical College, Dhaka, from January to December 2008, on 73 post mortem human thyroid gland collected from unclaimed dead bodies. Isthmus was found in 60 cases. The samples having the isthmus (n=60) were divided into three age-groups including group A (10-20 years), group B (21-50 years) & group C (>50 years) and the isthmus was cut off from the thyroid gland, then its length, breadth and thickness were measured and recorded. Results: The isthmus of the thyroid gland was found in 82.2% cases. It extended from 2nd to 4th tracheal ring in 91.7% and from 2nd to 5th ring in 8.3% cases. No difference was found in length, breadth and thickness of the isthmus of the thyroid gland in between males and females. However, difference was found in breadth between group A & B (p<0.05) and A & C (p<0.01) and in thickness between group B & C (p<0.05). Conclusion: The presence or absence, positional change and variation in gross dimension of the thyroid isthmus were evident in humans. The morphological difference was found with increasing age but not with sex. Nepal Journal of Medical Sciences | Volume 02 | Number 02 | July-December 2013 | Page 81-84 DOI: http://dx.doi.org/10.3126/njms.v2i2.8940